Gas dehydration process by using triethylene glycol and silica gel - Khairul Rafik, Abdullah (2009)
Gas dehydration is widely used in natural gas treatment plant as a common process, because water and hydrocarbon can form hydrates (ice formation) which may block valve and pipelines. Water also can cause corrosion in the presence of acid gas component in natural gas. Until today, the most popular dehydration process is adsorption and absorption process. The objective of this study was to remove the water content in natural gas for adsorption and absorption process. This study consists of fabricating the lab scale dehydration unit by using PVC-Clear pipe. Two types of desiccant were used in this study which is silica gel for adsorption process and triethylene glycol for absorption process. The various quantity of desiccant was used in this study to get the maximum amount of water content removal from natural gas. In this study, the methods used were designing, fabricating, testing, experimental and analyzing. From the study, the maximum allowable operating pressure for both dehydration unit is 0.3 bar. Furthermore, the higher quantity of desiccant gives the higher amount of water content removal from natural gas. The result also shows that the increasing operating pressure for the process will decrease the water content removal from natural gas for both processes. Lastly, triethylene glycol is a better desiccant compare with silica gel in dehydration process for this study.